Investigating the hidden costs of livestock guarding dogs and the diet of a sympatric predator in Namaqualand, South Africa - Kelly, Caitlin (Department of Biological Sciences, 2019)
The global decimation of carnivore populations has been called one of mankind’s most pervasive impacts on the natural world. Human-wildlife conflict over the threat (both real and perceived) predators pose to livestock is one of the leading causes of carnivore decline worldwide. Livestock guarding dogs have been widely acclaimed as an environmentally friendly tool for reducing this conflict, yet little is known about the hidden costs of their presence. This study used scat analysis to reconstruct the diet of livestock guarding dogs and local caracals (Caracal caracal) to better understand their impacts on biodiversity and livestock in Namaqualand, South Africa. For livestock guarding dogs, 187 scats revealed the consumption of (from most to least frequent): livestock, wild mammals (including ten native species), vegetation, anthropogenic items, invertebrates, reptiles, fruit and birds. However, the diet of dogs accompanied by a human attendant differed significantly (χ 2 = 94.075, p < 0.001) from dogs guarding sheep independently. While 75% of scats collected from dogs operating independently contained domestic ungulates, less than 5% of scats from dogs with a human attendant contained livestock. For caracals, 185 collected scats were analysed across two land uses: Namaqua National Park and surrounding farms. Eighteen mammalian prey species were identified in their overall diet, with medium sized (1-10 kg) mammals (particularly the rock hyrax, Procavia capensis) accounting for more than half of consumed prey (59.1%). Small mammals (<1 kg) and wild ungulates were consumed more frequently in the protected area than on farmland. Livestock comprised 16% of the mammalian biomass consumed on farms, however no livestock was found in caracal scat within the protected area. These results support a growing body of research that suggests caracals do not prefer livestock, but will consume them when their numbers are considerably higher than that of wild prey, as is the case on many farms. Although this analysis cannot differentiate between predation and scavenging, the results provide novel insight into the potential impacts of livestock guarding dogs on the landscape and their overall effectiveness as a nonlethal predator management tool. This can help inform livestock guarding dog training and predator management while providing key information about the diets of both an indigenous and introduced predator.